Analysis of the Romanian Educational Offer Regarding the Existing Situation at the Level of Specialization: Engineering and Management, and Business Administration - Andreea BARBU; Georgiana MOICEANU; Ştefan-Alexandru CATANĂ; Monica Claudia DUMITRA; Claudiu Adrian PURDESCU (Communications of International Proceedings, 2021)
This paper analyzes the Romanian educational offer regarding the existing situation at the level of specialization: Engineering and Management, and Business Administration. In this regard, it has been analyzed the 2020 educational offer regarding the bachelor programs within the Romanian cities. The results of this study highlighted that there are some important areas in the country where there are some special needs on the labor market regarding industrial and economic activity. In these areas, the educational offer is more diversified and the entrepreneurship culture is better promoted. In cities like Bucharest, Iasi, Cluj-Napoca, Timisoara, or Oradea, some faculties adapt their educational program to the needs of the local business environment, providing not only the transfer of theoretical knowledge in fields such as management, marketing, or engineering but also trying to combine these areas with the entrepreneurship and business side.
Keywords: Educational Offer; Entrepreneurship; Business Education; Business Administration; Engineering and Management